2020
DOI: 10.1038/s41467-020-15868-8
|View full text |Cite
|
Sign up to set email alerts
|

Solid solution for catalytic ammonia synthesis from nitrogen and hydrogen gases at 50 °C

Abstract: The lack of efficient catalysts for ammonia synthesis from N 2 and H 2 gases at the lower temperature of ca. 50°C has been a problem not only for the Haber-Bosch process, but also for ammonia production toward zero CO 2 emissions. Here, we report a new approach for low temperature ammonia synthesis that uses a stable electron-donating heterogeneous catalyst, cubic CaFH, a solid solution of CaF 2 and CaH 2 formed at low temperatures. The catalyst produced ammonia from N 2 and H 2 gases at 50°C with an extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 27 publications
2
78
0
Order By: Relevance
“…Extremely low‐temperature ammonia synthesis from H 2 and N 2 has been recently demonstrated using a Ru‐based catalyst by Hattori et al [ 107 ] Solid solution CaFH was used as the Ru catalyst support with an activity of 50 μmol g −1 h −1 achieved at ambient pressure and a near‐ambient temperature of 50 °C. CaFH support can be formed at low temperature from the solid solution of CaF 2 and CaH 2 ; the week ionic bonds in this solid solution between Ca 2+ and H − were attributed to the excellent catalytic performance by Hattori et al, [ 107 ] with the H − sites facilitating the release of hydrogen atoms.…”
Section: Ruthenium‐based Catalystsmentioning
confidence: 99%
“…Extremely low‐temperature ammonia synthesis from H 2 and N 2 has been recently demonstrated using a Ru‐based catalyst by Hattori et al [ 107 ] Solid solution CaFH was used as the Ru catalyst support with an activity of 50 μmol g −1 h −1 achieved at ambient pressure and a near‐ambient temperature of 50 °C. CaFH support can be formed at low temperature from the solid solution of CaF 2 and CaH 2 ; the week ionic bonds in this solid solution between Ca 2+ and H − were attributed to the excellent catalytic performance by Hattori et al, [ 107 ] with the H − sites facilitating the release of hydrogen atoms.…”
Section: Ruthenium‐based Catalystsmentioning
confidence: 99%
“…Misawa et al 9 developed a plasmon-induced technique for ammonia synthesis from N 2 that responded to visible light through a strontium titanate (SrTiO 3 ) photoelectrode loaded with gold nanoparticles. Masashi Hattori 10 et al reported a stable electron-donating heterogeneous catalyst, cubic CaFH to produce ammonia from N 2 and H 2 gases at 50 °C with an energy of 20 kJ·mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hosono group developed a novel cubic CaFH solid solution(a kind of hydride), which has ability to form NH 3 at 50 °C with very low activation energy of 20 kJ/mol [62] . This is the first report of any catalyst in NH 3 synthesis at lower temperature and pressure.…”
Section: Different Class Of Catalysts For Nh3 Synthesismentioning
confidence: 96%
“…[21,[63][64][65][66][67] In this regard, several binary nitrides of Mo, U, V and Re were explored. [58][59][60][61][62] Detailed mechanism of binary nitride in NH 3 synthesis is well documented in review by J Hargreaves. [21,68] Hence, current section is devoted to more recently explored ternary nitrides that are more stable and active compared to binary nitrides in NH 3 synthesis.…”
Section: Nitridesmentioning
confidence: 99%
See 1 more Smart Citation